Role of miRNA-23b as a biomarker of pediatric sepsis "A single-center study" - Hanaa I. Abd El-Hady; Shahenda Badran; Ahmed Ali; Alaa Nafea (Microbes and Infectious Diseases, 2024)
Background:  The COVID-19 pandemic caught the entire world off guard, leading countries across the globe to implement lockdown measures and resulting in a significant loss of life and physical impairment. The study aimed to assess the demographic factors affecting awareness, perception, and uptake of COVID-19 vaccines among students of a tertiary institution in northeastern Nigeria Methods: A cross-sectional study design was employed, and data were collected randomly through the administration of a structured questionnaire. Results: Among the study population, 451 (86.1%) were aware of COVID-19 vaccines. Of these, only 188(41.7%) had received the vaccine, while 263(58.3%) had not been vaccinated. Among the vaccinated, 119(63.3%) had received one of the five COVID-19 vaccines stated, while 69(36.7%) had no knowledge of the type of vaccine they had received. Of the 263(58.3%) unvaccinated respondents, 209(79.5%) attributed their hesitancy to a lack of trust in the vaccine. Although the positive perception of COVID-19 vaccines was higher than the negative perception among the respondents, but with no statistical difference (P=0.149). There was no significant relationship between respondents’ awareness of COVID-19 vaccines with their gender (P=0.3341), marital status (P=0.1657), and age group (P=0.0713), but religion showed a strong significant relationship (P=0.0015). There was no significant relationship between respondents’ perception of COVID-19 vaccines with gender (P=0.1885), marital status (P=0.5869), and religion (P=0.2286). Conclusion: These findings highlight the importance of tailored information campaigns addressing vaccine hesitancy, promoting accurate knowledge, and addressing safety concerns to increase vaccine acceptance and uptake among students in tertiary institutions.